Ecological Sustainability from a Legal Philosophy Perspective - Putro, Widodo Dwi; Bedner, Adriaan W. (Journal of Indonesian Legal Studies, 2023)
Gustav Radbruch made a fundamental contribution to legal thought, by suggesting the framework of legal justice, legal benefit, and legal certainty as the main purposes of law. This framework is widely accepted and still serves as a basis for thinking about questions of legal interpretation and the problems of legal positivism. This article argues that Radbruch’s framework falls short of addressing legal issues related to the threats of ecological crisis. Looking at legal theory and legal practice, we propose to add “sustainability” as a meta-value to Radbruch’s ideals of the legal system.